THE INFLUENCE OF THE FREQUENCY OF THE MAGNETIC FIELD ON THE STRUCTURE OF CAST IRON - A. G. Anisovich; L. V. Bislyuk; A. V. Azharonok; V. A. Kharkov; V. F. Bevza (Литьë и металлургия, 2012)
Research of influence of the magneto-impulse processing frequency on change of morphology of graphite inclusions of is carried out.